(untitled) (Applied Biological Research, 2025)
A study was conducted to assess the acute toxicity profile of Galium rotundifolium and Cirsium wallichii used @ 2000 mg kg-1 body weight. These plants, traditionally used in Uttarakhand (India) for liver health, were evaluated for immediate cytotoxic effects in Wistar rats. The randomized controlled trial included five female rats each in control and treatment groups, receiving the doses of 5, 50, 300, and 2000 mg kg-1 over a 15-day period. No visible signs of poisoning or fatalities were observed nor any haematological and biochemical parameter did show any signs of toxicity, thereby supporting the safety of these plant extracts. The oral administration of aqueous extracts from G. rotundifolium and C. wallichii appeared safe and well-tolerated in a single-dose study. However, further research is necessary to assess the potential long-term effects on organs. The extracts may possess hepato-protective, antioxidant, antibacterial, anti-inflammatory, analgesic, and anticancer properties, making them promising candidates for therapeutic applications.